DETERMINATION OF LUPEOL FROM MAKHAEN AT THAILAND AND TAIWAN BY HIGHPERFORMANCE LIQUID CHROMATOGRAPHY - TECHAOEI, SURACHAI; JARMKOM, KHEMJIRA; WISIDSRI, NAKUNTWALAI; THUNGMUNGMEE, SURADWADEE; KHOBJAI, WARACHATE (International Journal of Applied Pharmaceutics, 2019)
Objective: The objective of this research was to investigate the extraction and isolation of chemical compounds of Zanthoxylum limonella Alston extracts which selected from Chiang Mai and Pa Yao province, Thailand and Taiwan. Method: There are 3 locations of medicinal plant, Z. limonella Alston was collected, two provinces of northern Thailand, Chiang Mai and Phayao, including the other country, Taiwan. All of extractions were carried out by methanol. In this experimental study, thin-layer chromatography (TLC) and high-performance liquid chromatography (HPLC) were measured. Results: The result was found that the best organic solvent for extraction is methanol. The suitable of extraction was methanol and toluene in the ratio of 9:1 when developed with TLC and gradient methanol and water when analyzed with HPLC. The potential bioactive compound from crude extracted was lupeol. Crude extracted from leaf at Chiang Mai was highest lupeol as 5655.72 μg/mg extraction whereas crude extracted from leaf at Phayao showed this compound as 16, 98.81 μg/mg extraction. In addition, the crude extraction from root and bark of both areas showed the amount of lupeol less than leaf crude extracted. The further study will focus on antimicrobial activity and biological activity in the near future. Conclusion: The bioactive compound, lupeol was found in all part of Makhaen in Thailand but did not found in Taiwan seed.